Karakteristik Pengguna Antarmoda KRL – BRT Transjogja di Kawasan Stasiun Tugu Yogyakarta - Ayyasi, Salma; Dewi, Diah Intan Kusumo (Teknik PWK (Perencanaan Wilayah Kota), 2024)
One type of trip that needs to be observed is people who travel using more than one mode of public transportation to meet their daily needs. This can be found in KRL Commuter Line users who come from outside the region such as Surakarta and Klaten who carry out their activities within the scope of D.I Yogyakarta and its surroundings who of course transit in the Yogyakarta Tugu Station Area and continue their journey using the BRT Transjogja. By seeing those activities, the diversity of user characteristics needs to be considered. Therefore, this study aims to determine the characteristic of users of KRL-BRT Transjogja intermodal transportation in the Yogyakarta Tugu Station Area. By knowing the characteristics of these users, there will be a way to find out the basic needs of users regarding intermodal integration in transit areas. Data was collected by distributing questionnaire forms to a total of 96 respondents. The method used in this study is a quantitative method with the descriptive and frequency distribution analysis technique. The results of this study indicate that most of the users are workers followed by students who have productive age and are female with lower middle income from the regional minimum salary. It was also found that the use of intermodal by the presence of 2 dominant groups of workers who often use it during peak hours and college students who do not often use it during breaks. In addition, it was found that most users who use cashless payment methods have a high level of education. Then at the end of this study it was also found that the dominance of travel choices was using the Malioboro 1 bus stop by choosing routes 1A and 2A and many of them chose the mode of transportation at the end of the trip by walking.